2021
DOI: 10.1177/1368430221992126
|View full text |Cite
|
Sign up to set email alerts
|

Right-wing authoritarianism and social dominance orientation predict rejection of science and scientists

Abstract: Previous research has highlighted how ideological factors such as political self-identification, religiosity and conspiracy thinking influence our beliefs about scientific issues such as climate change and vaccination. Across three studies (combined N = 9,022) we expand on this line of inquiry to show for the first time that the ideological attitudes relating to authoritarianism and group-based dominance predict disagreement with the scientific consensus in several scientific domains. We show these effects are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 78 publications
8
49
0
1
Order By: Relevance
“…Using robust multiverse analyses, the authors found that controlling for all other factors, conservatism (assessed via operational ideology) was consistently amongst the most important predictors of not only denial of climate science, but also of general skepticism about science (vs. faith) and trust in ordinary people over experts. These findings are corroborated by Kerr and Wilson (2021) who show that SDO and RWA form a common origin to the various effects of ideology on distrust of science in the US and New Zealand. Using structural equation modelling, the authors demonstrate that individuals who hold stronger authoritarian and social inequality views find scientists less credible.…”
Section: General Science Attitudessupporting
confidence: 55%
“…Using robust multiverse analyses, the authors found that controlling for all other factors, conservatism (assessed via operational ideology) was consistently amongst the most important predictors of not only denial of climate science, but also of general skepticism about science (vs. faith) and trust in ordinary people over experts. These findings are corroborated by Kerr and Wilson (2021) who show that SDO and RWA form a common origin to the various effects of ideology on distrust of science in the US and New Zealand. Using structural equation modelling, the authors demonstrate that individuals who hold stronger authoritarian and social inequality views find scientists less credible.…”
Section: General Science Attitudessupporting
confidence: 55%
“…First, LWA emerges as an important predictor of vaccine-related attitudes: It predicts heightened COVID-19 concern, more vaccine acceptance, and higher support for vaccine mandates. Liberals generally place higher trust in science and express more positive attitudes toward various science issues than conservatives ( Kerr & Wilson, 2021 ; Peng, 2022 ). As the polarization of science intensifies, a pro-science view might have been integrated into the liberal political identity, thus making left-wing authoritarians more inclined to endorse pro-science positions.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, RWA might lead to more cautious responses to COVID-19 as RWA is associated with a worldview that sees the world as threatening and dangerous and deference to institutional authorities ( Duckitt et al, 2010 ). On the other hand, RWA is also associated with an anti-science attitude, adherence to the traditional way of life, obedience to conservative leaders ( Duckitt et al, 2010 ; Kerr & Wilson, 2021 ), which might make right-wing authoritarians less likely to respond to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Feygina et al, 2010). Recent studies support this claim by indicating that people on the political right are generally more inclined to reject scientific advice compared with people on the political left (Azevedo and Jost, 2021;Kerr and Wilson, 2021;Lewandowsky and Oberauer, 2021). In the United States, Conservatives are more inclined to downplay the risk of COVID-19 and less compliant with physical distancing measures (Grossman et al, 2020;Rosenfeld et al, 2020).…”
Section: Psychological Underpinnings Of Pandemic Denialmentioning
confidence: 99%